Menatap Dunia Kerja: Peran Career Adaptability Terhadap Self-Perceived Employability Pada Mahasiswa Tingkat Akhir Universitas Buana Perjuangan Karawang - Kalista Putri Suwandi; Nur Ainy Sadijah; Regi Ramadan (CV. Era Digital Nusantara, 2026)
Structural shifts in the economy during the Industry 4.0 era have transformed labor market demands. The high open unemployment rate among individuals aged 20–24, reaching 15.34% (BPS, 2024), underscores the urgency for final-year university students to develop a strong perception of their employability. This study aims to examine the effect of career adaptability on self-perceived employability among final-year students at Universitas Buana Perjuangan Karawang who are currently unemployed. A quantitative causal research design was employed, involving 326 students from the 2020, 2021, and 2022 cohorts, selected through quota sampling. Career adaptability was measured using the Career Adapt-Abilities Scale (CAAS), adopted and adapted by Sulistiani et al. (2018), while self-perceived employability was measured using the Self-Perceived Employability Scale for University Students, adapted from Rothwell et al. (2008). Data analysis was performed using simple linear regression in IBM SPSS Statistics 29. The results indicate that career adaptability has a positive and significant effect on self-perceived employability, with the regression equation SPE = 33.699 + 0.288CA, t = 9.746 (p < 0.001), and a coefficient of determination R² = 0.227. This suggests that career adaptability explains 22.7% of the variance in self-perceived employability, while 77.3% is influenced by factors beyond the scope of this study. Categorization shows that the majority of respondents fall into the moderate category for both variables. These findings emphasize the importance of developing career adaptability through structured career guidance programs in higher education to enhance students employability perceptions and readiness to enter a competitive workforce.